Pengetahuan dan Kesadaran Pengemudi Ojek Online Sebagai Determinan Perilaku Safety Riding - Laisyah Shava Zein Haryanto; Suherman Suherman; Irna Hasanah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
With the increasing number of online motorcycle taxi service users now, driving safety has become an important issue that needs more attention in online motorcycle taxis to reduce the risk of accidents. However, compliance of online motorcycle taxis in driving to implement safety riding is still a major problem due to the lack of awareness of the implementation of safety riding in online motorcycle taxi drivers. The influence of driver knowledge and awareness on safety riding behavior in online motorcycle taxi drivers must be understood and mastered properly and correctly by all online motorcycle taxi drivers so that the number of accidents does not increase and even the occupational health and safety of online motorcycle taxi drivers can be maintained. By adhering to the principles of safety riding, the occupational health and safety of online motorcycle taxi drivers will be maintained. The method used in this study is a literature study, by collecting and analyzing various relevant sources regarding knowledge, awareness, and driving behavior. The results of the study show that good knowledge of driving safety is positively related to safety riding behavior. In addition, awareness of the risk of accidents and the importance of obeying traffic rules also contribute significantly to reducing risky driving behavior. This study concludes that increasing driver knowledge and awareness through training and education can improve safety riding behavior, which in turn can reduce the number of accidents among online motorcycle taxi drivers. Suggestions are proposed for the implementation of periodic training programs for drivers to improve driving safety competence and awareness.